Handbook of Thin-Film Deposition Processes and Techniques Principles, Methods, Equipment and Applications. - Seshan, Krishna (Noyes Publications [Imprint] William Andrew, Inc. Elsevier Science & Technology Books [distributor], 2001)
Annotation This new edition traces the technology behind the growth in the silicon semiconductor industry and the continued trend in miniaturization, covering PVD, laser and E beam assisted deposition, MBE and ion beam methods. New chapters have been added on contamination and control, chemical mechanical polishing to attain the flatness required by modern lithography methods, new materials used for interconnect dielectric materials and meteorology.
Keywords: elektronické knihy; electronic books